2009
DOI: 10.1021/jp9025046
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Relaxation Dynamics of Au25L18 Monolayer-Protected Clusters

Abstract: I. Technical aspects of transient grating experimentsFemtosecond spectroscopy experiments are based on a Quantronix Q-lite seeded Integra C Titanium Sapphire amplifier generating 130 fs, 800 nm, 2.0 mJ laser pulses at 1 kHz. The laser system pumps two home-built noncollinear optical parametric amplifiers (NOPA). 1,2 The NOPA used for pump pulse generation has a spectral bandwidth corresponding to transform limited 15 fs laser pulses, whereas the NOPA from which probe pulses are derived generates spectra spanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
239
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(272 citation statements)
references
References 52 publications
31
239
2
Order By: Relevance
“…27,58,73 C. On the Mechanism of Emission. From the emission data, we can identify two luminescence transitions: transition from a short-lived state in the visible range, which is most probably associated with the MPC's core, 21,22,59,64 and that from a longlived surface-related state in near-infrared most probably associated with ligands. 21,22,59,64 Our time-resolved fluorescence data showed that the visible emission lifetime (∼250 fs, Figure 3) is substantially longer than the lifetime of the visible emission of larger nanoparticles.…”
Section: 24mentioning
confidence: 99%
See 4 more Smart Citations
“…27,58,73 C. On the Mechanism of Emission. From the emission data, we can identify two luminescence transitions: transition from a short-lived state in the visible range, which is most probably associated with the MPC's core, 21,22,59,64 and that from a longlived surface-related state in near-infrared most probably associated with ligands. 21,22,59,64 Our time-resolved fluorescence data showed that the visible emission lifetime (∼250 fs, Figure 3) is substantially longer than the lifetime of the visible emission of larger nanoparticles.…”
Section: 24mentioning
confidence: 99%
“…From the emission data, we can identify two luminescence transitions: transition from a short-lived state in the visible range, which is most probably associated with the MPC's core, 21,22,59,64 and that from a longlived surface-related state in near-infrared most probably associated with ligands. 21,22,59,64 Our time-resolved fluorescence data showed that the visible emission lifetime (∼250 fs, Figure 3) is substantially longer than the lifetime of the visible emission of larger nanoparticles. 59 The short-lived visible emission mechanism can be explained by the creation of the hole by the excitation in the ground state, which can be subsequently filled with the electron from the higher lying excited state near 2.5 eV (Figure 4, B band).…”
Section: 24mentioning
confidence: 99%
See 3 more Smart Citations